ENTREPRENEURIAL SMEs SURVIVING IN THE ERA OF MILLENNIALS AND LATER PERIOD: PROMOTING INVESTMENT GROUP (PGIs) AS SOLUTION - Ashar, Suci Rahmadani; Irfan, Irfan (Jurnal Iqtisaduna, 2019)
Entrepreneurial small and medium-sized (SMEs) is The Economic growth pillar that has a significant potential contribution toward economic development in Indonesian. In the millennial era, SMEs are required to be more competitive caused by Market imperfections and limited opportunities and they are still structural problems. In addition, inability in terms of leadership and management, lack knowledge of usage of technology that makes SMEs unable to develop in optimally to reach domestic and global markets. In fact, the government have not outline strategies to set the direction for economic development for SMEs in the next decade as current global, and digital economy will further allow SMEs to take advantage of new opportunities. The long term in future, SMEs will need the creativity of new market strategies, R & D and Know-well technology of information . For survive in the digital era and later period, A Promoting Investment Group (PIGs) is a solution to create new opportunities and SMEs strength. PIGs focused on mediating among SMEs and technology, markets and funds.